MOLECULAR DOCKING STUDIES AND ADME PREDICTION OF NOVEL ISATIN ANALOGS AS HIV-1-RT INHIBITORS WITH BROAD SPECTRUM CHEMO THERAPEUTIC PROPERTIES - Debnath, Biplab; Ganguly, Swastika (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Molecular docking studies were performed on 100 newly designed isatin analogs by using Glide v 5.0 on the active site of four different enzymes namely HIV-1 reverse transcriptase (PDB ID 1RT2), glucosamine 6-phosphate (GlcN6P) (PDB ID 2VF5), mycobacterium tuberculosis-CYP51 (PDB code 1EA1) and candida albicans (CACYP51) (PDB code chimeric-1EA1) to study the binding mode of these analogs to study the binding mode of these analogs. Binding mode analysis of the compounds with the highest docking scores (-8.31,-5.90,-7.16,-6.395 and -8.14) was carried out and were compared with that of the co crystallized ligands TNK651, glucosamine (GLP) and fluconazole(TPF) in the active sites ofÂ 1RT2, 2VF5,1EA1 , and chimeric 1EA1respectively. ADME properties of all the newly designed isatin analogs 1-100 was calculated by Qik Prop v3.0. All the designed compounds were found to exhibit lead like properties from the calculated ADME properties. Results of these docking analyses can be well used for the design and development of novel isatin analogs possessing HIV-1- RT inhibitory activity with broad spectrum chemotherapeutic properties. Â KEYWORDS Isatin analogs, Docking, HIV, NNRTIs , NNIBP , Lipinski's rule ,ADME